How to write a story - Phillips, Kathleen C. (New York : F. Watts, 1995)
Examines the basics of writing a story, from finding a title and beginning the work to completing and revising it.
Includes bibliographical references (p. 152-155) and index.
Young Adult
Keywords: Authorship -- Juvenile literature; Authorship; Creative writing; Authorship; Creative writing; Fiction -- Technique